PENERAPAN CASE BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR SPASIAL SISWA KELAS XII IPS DI MAN 2 KOTA PAYAKUMBUH - Mutiara Zenita; Nofrion (STKIP Subang, 2026)
This study aims to analyze the effect of implementing the Case-Based Learning model on improving the spatial thinking skills of 12th-grade social studies students at MAN 2 in Payakumbuh. This study employs a quantitative approach using a quasi-experimental design with a pretest-posttest control group. The sampling technique used is purposive sampling, which involves selecting a sample based on specific criteria. In determining the number of samples to be taken from each class, the researchers selected Class XII IPS 1 and Class XII IPS 4 as the research samples with the aim of obtaining a sample that represents the entire population of classes. The students in these sample classes possess the same competencies and abilities in the learning process, ensuring that the implementation of different learning models is not disrupted. Consequently, all 34 students in Class XII IPS 1 and all 34 students in Class XII IPS 4 were selected as the sample for this study. The research instrument was a test consisting of 30 items developed based on indicators of spatial thinking skills, including: Comparison, Aura, Region, Hierarchy, Transition, Analogy, Pattern, and Association. Based on the average posttest scores, the control class scored 69.24and the experimental class scored 81.39. This indicates that there was an improvement in learning outcomes alongside students’ spatial thinking skills, suggesting that the application of the Case-Based Learning model has a greater impact on improving learning outcomes and spatial thinking skills compared to conventional instruction. In terms of the increase in understanding (N-Gain) of the conceptual material on regions and regional zoning in spatial planning, the experimental class scored 0.71, which was higher than the control class’s score of 0.45. Subsequently, the hypothesis test yielded a calculated T-valueof 3,388> the critical T-value of 1.99 at a significance level of 0.05; therefore, Ha was accepted. It can be concluded that the implementation of the Case-Based Learning model has an effect on improving the spatial thinking skills of 12th-grade social studies students at MAN 2 Payakumbuh.